Postcolonial Expression in Music - Rai, Shraddha (Asian Journal of Science and Applied Technology, 2020)
Post colonialism forms a composite but a critical movement that renewed the perception and understanding of modern history, cultural studies, literature, and political economy. Although it started as an approach to the study of commonwealth literature, it broadened out to include other aspects of north-south relations making an impact on a wide variety of subjects including cultural studies, anthropology, geography, history, and politics. Despite the successful inclusion of the theory in the mentioned fields, the difficulty of mapping it in the field of International Relations (IR) is still evident.As a literary discourse, post colonialism, from the time of its entry to academia has incorporated various themes and issues in bourgeoning its growth. However, this attempt has considerably failed to get deserved attention. While the theory has continued the investigation into the ways in which the subaltern voices are silenced in both the local and global arena, little attention has been placed in the role of music. What this article, therefore, seeks to address is the relevance of music in an enhanced understanding of postcolonial theory. By and large, the zest of the article is to conceptualize music as a serious component of postcolonial theory and to explore a possibility wherein a meaningful linkage can be established between the two.